Development of Interactive Learning Media for Old Character Makeup in the Hair Styling and Fantasy Makeup Course - Puti Anggini, Saraskia; Supiani, Titin; Hidayah, Nurul (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop interactive learning media for old character makeup in the Hairdressing and Fantasy Makeup course, in order to overcome the limitations of existing media and increase student engagement. The research and development (RD) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model was used in this study. The media was developed using the Canva application, and data was collected through a Likert-scale questionnaire from material experts, media experts, and students. The results showed that this interactive learning media was very feasible and practical. The validity test by the material experts obtained a percentage of 94.67%, and by the media experts 97.33%, both in the